Pojav in zakorenitev romantičnega diskurza nedolžnega otroštva v britanskem in širšem evropskem prostoru - Burcar, Lilijana (Monitor ISH, 2007)
The article discusses the socio-political causes that led to the emergence and consolidation of the Romantic discourse of childhood innocence. It emphasises its inherent inconsistencies and argues that the Romantic discourse of innocence sequesters the child into a seemingly separate, static and timeless world of nature. The child is thus transformed into a blank and transcendent entity that appears to be floating free of historically and socially specific determinants. In this way, the child is emptied of its material specificities and denied the status of a subject.
Keywords: otroštvo; identiteta; nedolžnost; Romanticism; romantika; spol; seksualizacija